Healthy late preterm infants and supplementary artificial milk feeds: Effects on breast feeding and associated clinical parameters. Issue 4 (April 2015) - Mattsson, Elisabet; Funkquist, Eva-Lotta; Wickström, Maria; Nyqvist, Kerstin H.; Volgsten, Helena
Abstract: Objectives: to compare the influence of supplementary artificial milk feeds on breast feeding and certain clinical parameters among healthy late preterm infants given regular supplementary artificial milk feeds versus being exclusively breast fed from birth. Design: a comparative study using quantitative methods. Data were collected via a parental diary and medical records. Methods: parents of 77 late preterm infants (34 5/7–36 6/7 weeks), whose mothers intended to breast feed, completed a diary during the infants׳ hospital stay. Findings: infants who received regular supplementary artificial milk feeds experienced a longer delay before initiation of breast feeding, were breast fed less frequently and had longer hospital stays than infants exclusively breast fed from birth. Exclusively breast-fed infants had a greater weight loss than infants with regular artificial milk supplementation. A majority of the mothers (65%) with an infant prescribed artificial milk never expressed their milk and among the mothers who used a breast-pump, milk expression commenced late (10–84 hours after birth). At discharge, all infants were breast fed to some extent, 43% were exclusively breast fed. Key conclusions: clinical practice and routines influence the initiation of breast feeding among late preterm infants and may act as barriers to the mothers׳ establishment of exclusive breast feeding. Highlights: Clinical practice and routines influence the initiation of breast feeding among late preterm infants. Administration of regular artificial milk to late preterm infants and inadequate routines for support of mothers׳ early initiation of milk expression in hospital may act as barriers to mothers' establishment of exclusive breast feeding. Supplementary feeds exceeding the volume the infants would have received at the breast may negatively affect breast feeding.